2006
DOI: 10.1369/jhc.6a6944.2006
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression and Subcellular Localization of Claudin-7, −8, −12, −13, and −15 Along the Mouse Intestine

Abstract: (HY) S U M M A R Y Among tight-junction proteins, claudins, which play a key role in paracellular transport across epithelia, claudins 1 to 5 are expressed in the intestine, and changes in their abundance and/or distribution are considered to contribute to various gastrointestinal diseases. We investigated, by reverse transcription-PCR, immunoblot, and immunofluorescence analyses, which other claudin species were expressed in the mouse intestine, and whether they showed unique expression profiles. Rabbit po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
175
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(189 citation statements)
references
References 59 publications
14
175
0
Order By: Relevance
“…In mice, claudin-15 was detected among claudins with the highest expression in the colon (41) and it exhibited altered expression in the rat models of colitis and colitis-associated cancer (42). The current study also confirmed the differential expression between AC/AD and NC of two other genes encoding tight junction components: JAM2, a gene that has been found to be hypermethylated in AC (43), and CGN.…”
Section: Discussionsupporting
confidence: 78%
“…In mice, claudin-15 was detected among claudins with the highest expression in the colon (41) and it exhibited altered expression in the rat models of colitis and colitis-associated cancer (42). The current study also confirmed the differential expression between AC/AD and NC of two other genes encoding tight junction components: JAM2, a gene that has been found to be hypermethylated in AC (43), and CGN.…”
Section: Discussionsupporting
confidence: 78%
“…Several lines of evidence support a barrier-forming role for ZO-1, occludin, claudin-b, -c and -3 in fish [77,78], whereas claudin-12 and -15 in rats seem to possess pore-forming characteristics [79,80]. Moreover, the up-regulation of ZO-1 and occludin [81] and down-regulation of claudin-15 [82] attenuated the loss of the Fig.…”
Section: Trp Improved the Intestinal Barrier Function And Antioxidantmentioning
confidence: 97%
“…Therefore, we next investigated the effects of riboflavin on TJ complex and antioxidant system in the gills of fish. acted as barrier-forming TJ proteins in fish [22,23,73], whereas Claudin-12 and Claudin-15 acted as pore-forming TJ proteins in mice [74]. Moreover, studies showed that decreased Claudin-b, -3, Occludin and ZO-1 mRNA levels in fish [23], and up-regulated Claudin-12 and Claudin-15 gene expression in mice [75,76] impaired TJ barrier function.…”
Section: 23mentioning
confidence: 99%